1971
DOI: 10.1002/kin.550030106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen abstraction from organosilicon compounds. The reactions of fluoromethyl radicals with tetramethylsilane. Polar effects in gas phase reactions

Abstract: The photolysis of 1,1,3,3-tetrafluoroacetone has been reinvestigated as a source of CHFz radicals at temperatures up to 578'K, and the following rate constant ratio was determined for the reactions (8) (7)2CHF2 -+ CHFzCHFz* CHFz + CHFzCOCHFz -+ CHzFz + CF~COCHFZ log (k~/k~1'2)(mole-1'zcc1'2sec-1'2) = (4.73 f 0.18) -(11.26 f 0.40)/8* 1,l-Difluoro-and 1,1,3,3-tetrafluoroacetone were photolyzed in the presence of tetramethylsilane, and Arrhenius parameters were measured for the hydrogen abstraction re- By compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The oxidation products 25 and 26 are the lactones 25a and 26a for acrylic acid, 25b and 26b for methacrylic acid, the cyano esters 25c and 26c for acrylonitrile, a mixture of 25a and 26a and the acetic esters 25d and 26d for methyl acrylate, and the 7-hydroxy ketones 25e and 26e for methyl vinyl ketone. In all cases compounds 5 and 6…”
Section: R=ch2-^]mentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation products 25 and 26 are the lactones 25a and 26a for acrylic acid, 25b and 26b for methacrylic acid, the cyano esters 25c and 26c for acrylonitrile, a mixture of 25a and 26a and the acetic esters 25d and 26d for methyl acrylate, and the 7-hydroxy ketones 25e and 26e for methyl vinyl ketone. In all cases compounds 5 and 6…”
Section: R=ch2-^]mentioning
confidence: 99%
“…Internal consistency of the data was checked by eq 22. The results are summarized in Table I at 25 and 69 °C with the Arrhenius parameters deduced for acrylic acid, methyl acrylate, and acrylonitrile (Figure 6). These values differ somewhat in some cases from the ones previously reported1 and, in our opinion, are more exact because the kinetic model has less experimental error.…”
Section: R=ch2-^]mentioning
confidence: 99%
“…Under such conditions a linear relation between reaction enthalpy and activation energy is not expected. This sort of problem most likely manifests itself in H atom abstraction from silanes by fluoromethyl radicals which was studied by Kerr and Timlin [17]. These authors concluded that the E H values derived reflect contributions from polar and thermochemical factors.…”
Section: Comparison Of Experimental and Calculated D(xcci2-h) Values mentioning
confidence: 97%